PENGARUH BERAT MEDIA DAN INTERVAL PEMBERIAN PUPUK CAIR TERHADAP PERTUMBUHAN DAN HASILTANAMAN PAKCHOY DALAM POLIBAG - Daryanti Daryanti; Tyas Soemarah Koernia Dewi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2017)
Pakchoy (Brassica Chinensis L) or sawi sendok is one type of vegetabel which is much needed by Indonesian. Organik pakchoy cultivation could be done on limited land by using polybags. This research aims to know the impact of media volume and application of liquid fertilizer towards growth and yield of pakchoy plantation in the polybags. This research has been done at Desa Pojok, Kecamatan Mojogedang, Kabupaten Karanganyar on April 1 till May 6 2017. This research are using a complete randomized design with two different treatment. The first factor, media with code (B), consists of 3 extent i.e. B1 = 2 kg media (placed on 20x20 polybag size), B2 = 3 kg media (placed on 25x25 polybag size) and B3 = 4 kg media (placed on 35x35 polybag size). The media is soil mixed with solid organik fertilizer with proportion 1 : 1. The second treatment factor is the application interval of liquid organik fertilizer, coded as (P) consists of P0 = without treatment, P1 = once every five days, P2 = once every ten days. The result shows that : (1) The weight of the media has no significant effect toward height of the plant, the length of leaves, leaf width and dry weight of the plant, but it has distinctive impact on the number of leaves also fresh weight of the plant and the pakchoy consumption weight. (2) The application interval of liquid organik fertilizer has no significanteffect toward height of the plant and the length of leaves, it has effect toward leaf widht and dry weight of the plant also the number of leaves, fresh weight of the plant and consumption weight. (3) The combination of both treatment (weight of the media and application interval of liquid organik fertilizer) has no significant interaction with all of the growth parameters.